2021
DOI: 10.1021/acsami.1c17132
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Critical Role of Abundant-Porosity Supports in Polyethylenimine Functionalization as Efficient and Stable CO2 Adsorbents

Abstract: The emerging polyethylenimine (PEI)-functionalized solid adsorbents have witnessed significant development in the implementation of CO2 capture and separation because of their decent adsorption capacity, recyclability, and scalability. As an indispensable substrate, the importance of selecting porous solid supports in PEI functionalization for CO2 adsorption was commonly overlooked in many previous investigations, which instead emphasized screening amine types or developing complex porous materials. To this en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…The impact of different textural and morphological properties of the support on the CO 2 adsorption performance of the sorbent was demonstrated for physically impregnated amines [16] . Furthermore, more recently, Meng et al., shed light on the overlooked effect of porous supports of different composition on the cyclic stability of the sorbent [14e] . Nonetheless, further investigations into the underlying phenomena governing these observations are needed.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of different textural and morphological properties of the support on the CO 2 adsorption performance of the sorbent was demonstrated for physically impregnated amines [16] . Furthermore, more recently, Meng et al., shed light on the overlooked effect of porous supports of different composition on the cyclic stability of the sorbent [14e] . Nonetheless, further investigations into the underlying phenomena governing these observations are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the traditional amine solution CO 2 absorption method, solid amine CO 2 adsorbents have received extensive attention and exploration due to their advantages of low regeneration energy consumption, large adsorption capacity, and low corrosive action to equipment. ,, A large number of studies had shown that the adsorption performance of solid amines CO 2 adsorbents was mainly affected by factors including support type and pore structure, amine physicochemical property, amine loading amount, and external reaction conditions. Among them, the amine type is an important factor affecting the adsorption performance of solid amine adsorbents. Tetraethylenepentamine (TEPA) and polyethylenimine (PEI) are the two most studied and common organic amines, and the solid amine adsorbents derived from the TEPA or PEI have a higher CO 2 adsorption capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Solid adsorbents have received a great deal of attention due to their low energy consumption and relatively stable adsorption capacity. Various materials, including activated carbon, zeolites, MXenes, and metal–organic frameworks, have been widely explored due to their well-defined pore structures and high specific surface areas. However, the temperature dependence of physical adsorption leads to a rapid decrease in the adsorption capacity of these materials for CO 2 at high temperatures, limiting their industrial applications due to adsorption selectivity constraints. , To overcome the limitations of pure physical adsorption, a strategic combination of physical adsorption and chemical adsorption has been developed to improve the adsorption capacity. For example, organic amines loaded into porous supports have been widely studied as solid amine adsorbents for CO 2 capture in recent years, by which a reversible chemisorption between CO 2 and the amine functional groups can be readily achieved. Therefore, solid amine adsorbents exhibit excellent adsorption capacity, selectivity, and cycle ability and show good application potential in the field of postcombustion CO 2 capture.…”
Section: Introductionmentioning
confidence: 99%